A water-based zirconia ceramic slurry and a solidification molding method thereof
Patent Information
- Application Number
- CN202610851032.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-12
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]相较于传统油基陶瓷浆料,水基陶瓷浆料凭借绿色环保、制备成本低廉、作业安全性高等诸多优势,已然成为陶瓷凝固成型领域的主流研究方向,在水基陶瓷浆料凝固成型工艺体系中,无杂质引入前提下实现浆料精准、可控凝固,是制约该技术规模化落地的核心技术瓶颈,现有技术中通常通过调节pH值、外加电解质或有机交联剂等方式,促使陶瓷浆料完成凝固成型,但这些方法易引入杂质元素,影响氧化锆的相稳定性及最终材料的力学性能,此外,现有方法对凝固速率的调控能力有限,尤其是对于大尺寸或复杂形状部件,容易出现凝固速率不可控、坯体内应力集中、开裂等问题,基于此,现在提供一种水基氧化锆陶瓷浆料及其凝固成型方法,可以消除现有技术存在的弊端
[0022]1、本发明通过将碘酸钙的粒度作为独立变量,碘酸钙粒度与温度进行协同调控的方式,实现水基氧化锆陶瓷浆料凝固速率在4~60min范围内的灵活调节,从而能够满足从小尺寸快速成型到大尺寸复杂结构部件的多样化工艺需求。
Smart Images

Figure CN122977836A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic material forming technology, specifically a water-based zirconia ceramic slurry and its solidification forming method. Background Technology
[0002] Zirconia ceramics are widely used in structural ceramics, medical devices and electronic components due to their excellent mechanical properties, wear resistance and biocompatibility. With the upgrading of industrial technology in various fields, the market requirements for the specifications and shapes of zirconia ceramic products are gradually increasing. The efficient molding and preparation of large-size and irregularly shaped complex zirconia ceramic parts has become a technical pain point that the precision ceramic processing industry urgently needs to overcome.
[0003] Compared to traditional oil-based ceramic slurries, water-based ceramic slurries have become the mainstream research direction in the field of ceramic solidification molding due to their numerous advantages, such as being environmentally friendly, having low preparation costs, and being safe to operate. In the solidification molding process of water-based ceramic slurries, achieving precise and controllable solidification of the slurry without the introduction of impurities is the core technical bottleneck restricting the large-scale implementation of this technology. Existing technologies usually promote the solidification molding of ceramic slurries by adjusting the pH value, adding electrolytes or organic crosslinking agents, etc. However, these methods are prone to introducing impurity elements, affecting the phase stability of zirconia and the mechanical properties of the final material. In addition, existing methods have limited ability to control the solidification rate, especially for large-sized or complex-shaped parts, which can easily lead to problems such as uncontrollable solidification rate, stress concentration in the green body, and cracking. Based on this, a water-based zirconia ceramic slurry and its solidification molding method are provided, which can eliminate the drawbacks of existing technologies. Summary of the Invention
[0004] The purpose of this invention is to provide a water-based zirconia ceramic slurry and its solidification molding method to solve the problems in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] A method for solidifying and molding a water-based zirconia ceramic slurry, comprising the following steps:
[0007] Step 1: Low-temperature locking: Mix calcium iodate with water at 0℃~10℃ to form a suspension, wherein the particle size of calcium iodate is... The range is 0.1–20 μm;
[0008] Step 2: Slurry preparation: Add zirconium oxide ceramic powder and dispersant to the suspension obtained in Step 1, stir evenly to obtain ceramic slurry;
[0009] Step 3: Molding and curing: The ceramic slurry obtained in step 2 is injected into the mold. The temperature of the slurry is raised to 20℃~70℃ by heating. Calcium iodate dissolves at a corresponding rate based on its selected particle size and releases calcium ions. The calcium ions interact with the surface charge of the powder to cause the slurry to solidify in situ, forming a ceramic green body. The solidification time is 4~60min.
[0010] Step 4: Post-processing: Demold, dry and sinter the solidified green body to obtain zirconia ceramic parts.
[0011] Based on the above technical solutions, the present invention also provides the following optional technical solutions:
[0012] In one alternative: the solidification rate of calcium iodate in step one is controlled by selecting or mixing different particle sizes, when the calcium iodate... When the particle size is ≤1μm, the solidification time is 4–20 min. When calcium iodate… For particles ≥5μm, the solidification time is 30–60 min.
[0013] In one alternative: the calcium iodate in step one is a mixture of two or more different particle sizes, with the fine-particle component... ≤1μm, coarse-grained components ≥5μm, the mass ratio of the two is 1:5 to 1:1.
[0014] In one alternative: the amount of calcium iodate added in step one is 0.05 to 0.3 wt% of the slurry.
[0015] In one alternative: the water in step one is deionized water, and the pH of the concentrated ammonia solution is adjusted to a range of 9.0–11.5.
[0016] In one alternative: the zirconia ceramic powder in step two is one of 3Y-TZP, 5Y-PSZ, or other zirconia powders containing stabilizers, with a powder particle size of... The range is 0.2–10 μm.
[0017] In one alternative: the dispersant in step two is one or more of ammonium polyacrylate, polyethylene glycol or ammonium citrate, and the amount of dispersant added accounts for 0.2 to 1.0 wt% of the powder.
[0018] In one alternative: the heating method in step three includes one or more of the following: preheating the mold, infrared heating, and microwave heating.
[0019] In one alternative: 3Y-TZP is a 3 mol% yttrium oxide stabilized tetragonal zirconia polycrystalline ceramic, and 5Y-PSZ is a 5 mol% yttrium oxide partially stabilized zirconia.
[0020] The present invention also discloses a water-based zirconia ceramic slurry, which is prepared by the above-described method.
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0022] 1. This invention achieves flexible adjustment of the solidification rate of water-based zirconia ceramic slurry within the range of 4 to 60 minutes by treating the particle size of calcium iodate as an independent variable and coordinating the particle size of calcium iodate with temperature. This enables the flexible adjustment of the solidification rate of the slurry to meet the diverse process requirements from small-size rapid prototyping to large-size complex structural components.
[0023] 2. This invention achieves slow solidification by using large-particle calcium iodate, or by using a mixture of fine and coarse-particle calcium iodate to achieve gradient solidification from the mold wall to the center, effectively avoiding internal stress, deformation and cracking caused by excessively rapid solidification, and significantly improving the yield of large-size and complex-shaped ceramic blanks.
[0024] 3. This invention utilizes calcium ions released from calcium iodate to dissolve into the zirconium oxide lattice at high temperature as a stabilizer, thereby avoiding the introduction of foreign impurity elements and helping to maintain the material purity, phase stability and final mechanical properties of zirconium oxide ceramics.
[0025] 4. This invention locks calcium ions at low temperatures within the range of 0℃ to 10℃ and releases them in a particle-dependent manner after heating. This simple process design ensures precise control over the coagulation behavior of slurry while maintaining an environmentally friendly and low-cost water-based system. It is easy to operate and has a wide range of applications. Attached Figure Description
[0026] Figure 1 This is a schematic diagram of the solubility of calcium iodate as a function of temperature according to the present invention.
[0027] Figure 2 This is a schematic diagram illustrating the change in conductivity over time of calcium iodate with different particle sizes in aqueous solution according to the present invention. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0029] Example 1
[0030] A method for solidifying and molding a water-based zirconia ceramic slurry, comprising the following steps:
[0031] Rapid prototyping applications:
[0032] Take 100g of 3Y-TZP zirconia powder (particle size) =0.5μm), dispersant ammonium polyacrylate 0.8g, calcium iodate 0.2g ( =0.36μm), 40mL of deionized water (pH adjusted to 9.8);
[0033] First, calcium iodate and deionized water are stirred and mixed evenly at 4°C to form a suspension. Then, zirconium oxide powder and dispersant are added, and stirring is continued for 30 minutes to obtain a slurry with good flowability.
[0034] Pour the slurry into a mold with a release agent on the inner wall (the mold is preheated to 40°C), control the relative humidity of the environment at 50%, and let it stand for 8 minutes until the slurry is completely solidified.
[0035] After demolding, the blank is dried and sintered at 1500℃ to obtain a dense zirconia ceramic part with a density of 6.05 g / cm³, free from cracks and deformation.
[0036] Example 2
[0037] A method for solidifying and molding a water-based zirconia ceramic slurry, comprising the following steps:
[0038] Applications of large-size thin-walled parts and different powder systems:
[0039] Take 100g of 5Y-PSZ zirconia powder (particle size) =2.3μm), dispersant ammonium citrate 0.3g, calcium iodate 0.3g ( =8.9μm), 40mL of deionized water (pH adjusted to 10.5);
[0040] First, mix calcium iodate with deionized water at 4°C, then add powder and dispersant and stir until homogeneous;
[0041] The slurry is injected into a large-sized, thin-walled, complex-shaped mold. Infrared heating is used to raise the surface temperature of the mold to 50°C. The relative humidity of the environment is controlled at 60%. The mold is kept at this temperature for 35 minutes until the slurry is completely solidified.
[0042] The subsequent processing is the same as in Example 1. The resulting ceramic component has a smooth surface, no deformation or cracks, and a bending strength of 950 MPa.
[0043] Example 3
[0044] A method for solidifying and molding a water-based zirconia ceramic slurry, comprising the following steps:
[0045] Applications of mixed particle size gradient solidification:
[0046] Take 100g of 3Y-TZP zirconia powder (particle size) =0.8μm), dispersant polyethylene glycol 0.6g, calcium iodate 0.25g, of which fine particles ( =0.36μm) and coarse grains ( =8.9μm) mass ratio 1:2, 40mL deionized water (pH adjusted to 10.8);
[0047] After being mixed evenly at 4℃, the mixture is poured into the mold. The mold is preheated to 40℃ and the relative humidity of the environment is controlled at 55%. The fine calcium iodate particles dissolve rapidly, triggering initial solidification (solidification occurs first near the mold wall). The coarse particles continuously release calcium ions, achieving gradient solidification from the surface to the interior, effectively avoiding cracking in the center of large-sized blanks due to solidification shrinkage.
[0048] After drying and sintering, the green body has a uniform internal structure and no defects, with a solidification time of 25 minutes.
[0049] Example 4
[0050] A method for solidifying and molding a water-based zirconia ceramic slurry, comprising the following steps:
[0051] Microwave heating rapid prototyping applications:
[0052] Take 100g of 3Y-TZP zirconia powder (particle size) =0.3μm), dispersant ammonium polyacrylate 1.0g, calcium iodate 0.15g ( =0.22μm), 40mL of deionized water (pH adjusted to 9.8);
[0053] After being mixed evenly at 4℃, the mixture is poured into a mold and microwave heating is used to rapidly raise the temperature of the slurry to 60℃. The relative humidity of the environment is controlled at 45%, and the slurry is completely solidified within 5 minutes.
[0054] After drying and sintering, the green body has a density of 6.07 g / cm³ and a bending strength of 1180 MPa.
[0055] Example 5
[0056] A method for solidifying and molding a water-based zirconia ceramic slurry, comprising the following steps:
[0057] Medium particle size, medium-speed curing applications:
[0058] Take 100g of 3Y-TZP zirconia powder (particle size) =1.5μm), dispersant ammonium polyacrylate 0.4g, calcium iodate 0.2g ( =3.5μm), 40mL of deionized water (pH adjusted to 10.2);
[0059] After mixing evenly at 4℃, the mixture is poured into the mold. The mold is preheated to 70℃ and the relative humidity is 55%. The mixture is left to stand for 15 minutes until it is completely solidified.
[0060] After drying and sintering, the green body has a density of 6.06 g / cm³ and a bending strength of 1120 MPa.
[0061] Example 6
[0062] A method for solidifying and molding a water-based zirconia ceramic slurry, comprising the following steps:
[0063] Verification of slow setting of large particles:
[0064] Take 100g of 3Y-TZP zirconia powder (particle size) =0.8μm), dispersant ammonium polyacrylate 0.5g, calcium iodate 0.1g ( =18.7μm), 40mL of deionized water (pH adjusted to 10.0);
[0065] After mixing evenly at 4℃, the mixture is poured into the mold. The mold is preheated to 40℃, the relative humidity of the environment is controlled at 50%, and the mixture is left to stand for 50 minutes until it is completely solidified.
[0066] After drying and sintering, the green body has a uniform internal structure and a smooth surface without cracks.
[0067] This embodiment demonstrates that even when using large-particle-size calcium iodate close to the upper limit, a qualified green body can still be successfully prepared by this method.
[0068] The following experimental examples are mechanism verifications of the core innovation of this invention. They aim to demonstrate, through rigorous single-variable experiments, the regulatory effect of calcium iodate particle size as an independent variable on solidification time, and its synergistic effect with temperature.
[0069] To indirectly characterize the ion release rate of calcium iodate with different particle sizes in aqueous solution, the conductivity method was used. Changes in conductivity reflect real-time changes in calcium ion concentration in the solution; a faster increase in conductivity indicates a faster rate of calcium iodate dissolution and release of calcium ions.
[0070] Experimental Example 1
[0071] Single-variable verification of the effect of calcium iodate particle size on slurry setting time:
[0072] To verify the effect of calcium iodate particle size as an independent variable on solidification time, this experimental example strictly controlled all parameters except for calcium iodate particle size to remain constant. The specific conditions are as follows:
[0073] Take 100g of 3Y-TZP zirconia powder (particle size) =0.8μm), dispersant ammonium polyacrylate 0.5g, calcium iodate 0.1g (0.07wt% of slurry), deionized water 40mL (pH adjusted to 10.0), mixed at 4℃ and then poured into the mold. The mold was preheated to raise the slurry temperature to 40℃, and the relative humidity of the environment was controlled at 50%.
[0074] Under identical conditions, only the calcium iodate particle size was changed. The solidification endpoint was defined as the slurry losing its fluidity, showing no surface collapse, and leaving no indentation when lightly touched with a needle tip. The experimental results are as follows:
[0075]
[0076] Results Analysis: Under the condition of strictly fixed single variables such as powder type, particle size, dispersant type and dosage, solid content, initial and curing temperatures, and ambient humidity, with the increase of calcium iodate... As the thickness increased from 0.22 μm to 18.7 μm, the solidification time significantly increased from 4 min to 50 min;
[0077] This experiment directly and powerfully demonstrates that calcium iodate particle size is a key variable, independent of the other factors mentioned above, that can effectively regulate the calcium ion release rate and slurry coagulation behavior.
[0078] Experiment Example 2
[0079] Verification of the synergistic effect of temperature and calcium iodate particle size:
[0080] Using the exact same slurry formulation as in Experiment 1 (powder, dispersant, water content, and pH value were all fixed), two groups of typical calcium iodate particle sizes were selected, and molding experiments were conducted at different curing temperatures. The complete solidification time was recorded, and the results are as follows:
[0081]
[0082] Results analysis: Experimental data show that for calcium iodate of the same particle size, increasing the curing temperature significantly shortens the solidification time, which is consistent with the law that the solubility of calcium iodate increases with increasing temperature. However, at any same curing temperature, the solidification time of the coarse-grained group (8.9 μm) is significantly longer than that of the fine-grained group (0.36 μm).
[0083] This result intuitively reveals that particle size has an independent effect on the setting rate. Through the dual synergistic control of particle size and temperature, the setting curve of the slurry can be precisely preset within an extremely wide time window (4 to 48 minutes in this experimental example). This kind of process flexibility cannot be achieved by existing technologies that rely solely on temperature regulation.
[0084] Comparative Example 1
[0085] According to Example 1, where calcium iodate is omitted, and only zirconium oxide powder, dispersant and water are used to prepare a slurry under the same conditions, after being injected into a mold and placed in the same environment, the slurry never solidifies and cannot be molded.
[0086] The above description is merely a specific embodiment of this disclosure, but the scope of protection of this disclosure is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this disclosure should be included within the scope of protection of this disclosure. Therefore, the scope of protection of this disclosure should be determined by the scope of the claims.
Claims
1. A method for solidifying and molding a water-based zirconia ceramic slurry, characterized in that, Includes the following steps: Step 1, Low-Temperature Locking: Calcium iodate is mixed with water at 0℃~10℃ to form a suspension, wherein the particle size of the calcium iodate is... The range is 0.1–20 μm; Step 2, Slurry preparation: Add zirconium oxide ceramic powder and dispersant to the suspension obtained in Step 1, stir evenly to obtain ceramic slurry; Step 3, Molding and Curing: The ceramic slurry obtained in Step 2 is injected into the mold. The temperature of the slurry is raised to 20℃~70℃ by heating. Calcium iodate dissolves at a corresponding rate based on its selected particle size and releases calcium ions. The calcium ions interact with the surface charge of the powder to induce in-situ solidification of the slurry, forming a ceramic green body. The solidification time is 4~60min. Step 4, Post-processing: Demold, dry, and sinter the solidified green body to obtain zirconia ceramic parts.
2. The solidification and molding method of a water-based zirconia ceramic slurry according to claim 1, characterized in that, In step one, the solidification rate of calcium iodate is controlled by selecting or mixing different particle sizes. When the particle size is ≤1μm, the solidification time is 4–20 min. When calcium iodate… For particles ≥5μm, the solidification time is 30–60 min.
3. The solidification and molding method of a water-based zirconia ceramic slurry according to claim 1, characterized in that, The calcium iodate in step one is a mixture of fine and coarse particles, with the fine particle component... ≤1μm, coarse-grained components ≥5μm, the mass ratio of the two is 1:5 to 1:
1.
4. The solidification and molding method of a water-based zirconia ceramic slurry according to claim 1, characterized in that, The amount of calcium iodate added in step one is 0.05 to 0.3 wt% of the slurry.
5. The solidification and molding method of a water-based zirconia ceramic slurry according to claim 1, characterized in that, The water used in step one is deionized water, and the pH of the concentrated ammonia solution is adjusted to a range of 9.0–11.
5.
6. The solidification and molding method of a water-based zirconia ceramic slurry according to claim 1, characterized in that, The zirconia ceramic powder in step two is zirconia powder containing a stabilizer, and the powder particle size is... The range is 0.2–10 μm.
7. The solidification and molding method of a water-based zirconia ceramic slurry according to claim 1, characterized in that, The dispersant in step two is one or more of ammonium polyacrylate, polyethylene glycol, or ammonium citrate, and the amount of dispersant added accounts for 0.2 to 1.0 wt% of the powder.
8. The solidification and molding method of a water-based zirconia ceramic slurry according to claim 1, characterized in that, The heating method in step three includes one or more of the following: preheating the mold, infrared heating, and microwave heating.
9. A water-based zirconia ceramic slurry, characterized in that, Prepared by the method described in any one of claims 1-8.